Skills Training for Students with Special Needs Using Skills Worksheets And Snack Processing Videos - Siti Sulandjari; Rahayu Dewi; Satwika Arya Pratama (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
Children with special needs have several characteristics including difficulty communicating, learning difficulties, not easy to follow orders, emotional, difficult to write or read, behave according to habits, like to imitate, high sensitivity, and introvert. Children with special needs need more attention. The Lentera Fajar Indonesia Community Learning Activity Center (PKBM) is an institution that accommodates children with special needs aimed at providing assistance, guidance, and independence from an early age. This activity aims to determine whether snack processing education using Skill Worksheets (LKK) and Video can be used as a means to stimulate and train the skills of students with special needs. The method used in this activity is a demonstration method using media in the form of worksheets and video snack processing. . The results obtained from the activity are: 1) snack processing education using LKK and video tutorials followed by demonstrations at each processing stage and followed directly by students causing students' interest and enthusiasm to take part in each processing stage, 2) student learning resistance increases up to 40%, namely from 90 minutes to 150 minutes without leaving the study area, 3) students need assistance from accompanying teachers in understanding the contents of skill worksheets, 4) the use of Skills Worksheets and videos to train motor skills was responded positively by accompanying teachers with suggestions for increasing the volume of the voice. adjust to the child's condition.